Extraction and physicochemical characterization of pectin of rose grape Red Globe variety - Laborde, Mariana Belén (2020)
In order to generate useful information for the food industry, adding value to the national production chain of a ?commodity?, physico-chemical characteristics of the pectins extracted from the Red Globe rose grape were evaluated using several analytical methods and compared to commercial pectin. From this analysis, it was inferred that pectin of Red Globe grape are of low methoxyl grade, taking into account the behaviour of the characteristic signals for the esterified (COO-R, 1745 cm-1) and free (COO-, 1 640 cm-1) carboxyl groups and the area ratio of the Fourier transform infrared spectra. These results were in agreement with the analytical determinations of equivalent weight (1441.32 ± 15.92 mg·meq-1), free acidity (0.69 ± 0.01 meq·g-1), degree of methoxylation (1.7 ± 0.1 %), degree of esterification (44.7 ± 1.3 %) and anhydrous galacturonic acid percentage (34.6 ± 0.6 %). These grape pectin characteristics are suitable for obtaining jellies or jams with low sugar content, adding value to the primary production chain.